2020
DOI: 10.1002/adem.201901558
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical Characterization of Ce0.8Gd0.2O2‐δ–FeCo2O4 Dual Phase Oxygen Transport Membranes

Abstract: Oxygen transport membranes, which exhibit an almost 100% permeation selectivity regarding oxygen, [1] are a promising option to realize environmental-friendly, economically sound, and efficient processes for pure oxygen production, [1-4] oxycombustion, [5-7] and conversion of carbonaceous products. [8-12] These applications typically involve harsh environments, in particular high temperatures, and oxygen partial pressure gradients as well as the exposure to flue gas, which can be detrimental to the chemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Copyright 2019 Elsevier. [104] Furthermore, the same group reported that, at the optimum sintering temperature of 1200°C, Ce 0.8 Gd 0.2 O 2-δ -FeCo 2 O 4 microstructure exceeded 99% density with few surface defects and exhibited a high average flexural strength of~266 MPa. Sintering at this temperature contributes to the homogenization of the pore distribution and a higher density along with improved homogeneity of pore distribution result in enhanced mechanical strength.…”
Section: Dual Phase Membranesmentioning
confidence: 97%
See 3 more Smart Citations
“…Copyright 2019 Elsevier. [104] Furthermore, the same group reported that, at the optimum sintering temperature of 1200°C, Ce 0.8 Gd 0.2 O 2-δ -FeCo 2 O 4 microstructure exceeded 99% density with few surface defects and exhibited a high average flexural strength of~266 MPa. Sintering at this temperature contributes to the homogenization of the pore distribution and a higher density along with improved homogeneity of pore distribution result in enhanced mechanical strength.…”
Section: Dual Phase Membranesmentioning
confidence: 97%
“…Ceramic oxide transport membranes due to their 100% selectivity to oxygen, find wide range of applications in areas of pure oxygen production, carbon capture/ storage, petrochemical processes and oxy-combustion. [102][103][104][105][106] [102] for oxygen transport. [106] According to recent reports, Ce 0.8 Gd 0.2 O 1.9 as ionic conducting phase, promised mechanical and chemical stability in corrosive atmospheres (e. g., SO 2 , CO 2 ) at elevated temperature (~850°C).…”
Section: Dual Phase Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…Dual-phase membranes with FeCo 2 O 4 , or its iron-rich pendant Fe 2 CoO 4 , and Gd-doped ceria as an ion conductor have already been successfully applied as oxygen permeation membranes with high permeability in the temperature range above 800 °C [10][11][12], and microstructural as well as mechanical investigations and optimizations have been performed [13][14][15]. Especially for FeCo 2 O 4 addition, the development of an additional electron-conductive phase (namely (Ce,Gd)(Fe,Co)O 3 ), whose composition and abundance depends on the ceria/spinel ratio, has recently been discussed [16].…”
Section: Introductionmentioning
confidence: 99%